Hip muscle strength asymmetries and their associations with hip morphology and symptoms are sex-specific in patients with femoroacetabular impingement syndrome. (March 2020) - Maffiuletti, Nicola A.; Bizzini, Mario; Sutter, Reto; Pfirrmann, Christian W.; Naal, Florian D.; Leunig, Michael; Casartelli, Nicola C.
Abstract: Objectives: To investigate sex-specific differences in hip muscle strength asymmetries, and associations between hip abductor and flexor strength asymmetries, hip morphology and symptoms in patients with femoroacetabular impingement syndrome (FAIS). Design: Cross-sectional study. Setting: Clinical setting. Participants: Thirty-four patients with FAIS (21 women, 13 men). Main outcome measures: Side-to-side strength asymmetries of hip adductor, abductor, internal and external rotator, flexor and extensor muscles were assessed using dynamometry, while hip pain during contractions was evaluated with a visual analogue scale. Hip morphology was assessed on anteroposterior pelvic radiographs and magnetic resonance arthrography images. Hip symptoms were evaluated using the Oxford Hip Score (OHS). Results: Women presented larger hip flexor strength asymmetries than men. In women, hip abductor asymmetries correlated with the OHS and with hip pain during muscle contraction. Hip flexor asymmetries correlated with the alpha angle in men. Conclusion: Patients with FAIS demonstrated sex-specific hip muscle strength asymmetries and associations with the underlying hip symptoms and morphology. Women showed larger hip flexor strength asymmetries than men, and their hip abductor strength asymmetries were associated with hip symptoms. In contrast, hip flexor strength asymmetries in men were associated with the severity of the underlying cam morphology. Highlights: Women with FAIS demonstrate larger strength asymmetries than men in the hip flexors. Hip abductor strength seems to be associated to the extent of hip symptoms in women. Hip flexor strength seems to be associated to cam morphology severity in men.